Molecular species delimitation of reef-building coral genera, Porites and Turbinaria (Anthozoa: Scleractinia), from the intertidal fringing reefs of Gulf of Kutch, India reveals unrecognized diversity. Issue 6 (18th August 2019) - Shimpi, Gaurav G.; Patel, Neha P.; Haldar, Soumya
Abstract : Knowledge of extant biodiversity with accurate species boundaries is one of the crucial prerequisites for guiding conservation priorities in the face of global climate change. DNA taxonomy promises to provide a rapid and reliable tool for species delimitation of morphologically challenging taxa, such as reef-building corals. Despite harbouring diverse coral assemblages, molecular studies of hard corals occurring in the seas around India are lacking. The Gulf of Kutch (GoK), located in the north-western part of India, is one such region. Information on coral species inhabiting this unique ecosystem is limited to morphology, which is often highly variable and phenotypically plastic, obscuring species boundaries. Here, we present the first exploration of molecular divergence of hard corals of the GoK in order to identify evolutionarily distinct lineages. Nuclear ribosomal ITS and mitochondrial COI markers were sequenced for samples of dominant genera, Porites and Turbinaria for phylogenetic comparisons with available data from other ecosystems of the world. Five molecular species delimitation methods were applied to the datasets and their performance was evaluated. Our analyses clearly suggest the occurrence of unique genotypes of both these genera in the GoK, unequivocally discerned by all the five methods as well as microskeletal features. This first integrative assessment provides implications for the phylogeny of these genera and identifies previously unrecognized scleractinian species hidden in the GoK ecoregion.